(untitled) (Research, Society and Development, 2022)
The reutilization of agro-industrial by-products for obtaining of high-value added biosurfactants is a promising approach for minimizing the total production costs. In this context, this study aimed to evaluate the production of biosurfactant by the Mucoralean fungus Syncephalastrum racemosum UCP 1302, by bioconversion of renewable substrates: cassava wastewater (CWW), waste soybean oil (WSO) and corn steep liquor (CSL). For this, a 23 full-factorial design (FFD) was applied and the results showed the ability of this strain to produce biosurfactant in all conditions of the FFD, standing out the condition 7 due to the greatest reduction of surface tension (from 72 to 30.9 mN/m). Preliminary characterization showed the lipopeptide nature of the biomolecule, as well as its anionic character and critical micellar concentration (CMC) of 1.25 mg/ml. Biotensoactive demonstrated stability to variations of temperature, pH and NaCl concentrations, wettability in polyester textile and it was effective on reduction of viscosity of burned motor oil. Hence, S. racemosum showed excellent ability to produce biosurfactant by green bioconversion of low-cost substrates, making the bioprocess economical and enabling its biotechnological applications.